Analisis E-Commerce Sebagai Ekonomi Digital Dalam Mendorong Pertumbuhan Perekonomian Di Indonesia - Anisa Novia Rahmadani; Aqila Zahra Aziz; Dwi Indriani; Jihan Fairuz; Zalika Sabina; Diwayana Putri Nasution (Institut Nalanda, 2024)
The aim of this research is to see the impact of the growth of e-commerce on business people, consumers and society, as well as the extent to which this growth drives the regional economy in Indonesia. The research uses the literature study method. Briefly, e-commerce is trade in which the intermediaries are electronic devices connected to each other in a virtual space. Both business people, consumers and society benefit greatly from E-Commerce. In the end, this impact will encourage regional economic growth directly and indirectly, but can also cause economic inequality, especially economic backwardness due to lack of electricity.